Analysis of The Impact of The Region Expansion on Economic Growth (Case Study: Expansion of North Toraja Regency from Tana Toraja) - Tapparan, Samuel Randy; Wahab, Abdul (Jurnal Office, 2019)
The increasing number of regions proposing themselves to form new autonomous regions since the enactment of Law Number 32 of 2004 concerning "Regional Government", aims to improve economic development and the welfare of the people in each region. The purpose of this study was to analyze the impact of regional expansion on the economic growth of North Toraja Regency. The Technik of data collection in this study uses the documentary Technik, which is in the form of reports from relevant agencies. The analysis technique used is by using the independent sample T-test. The results of the study show that regional expansion has an impact on the economic growth of North Toraja Regency.